A first-in-class and a fished out anticancer platinum compound: cis-[PtCl2(NH3)2] and cis-[PtI2(NH3)2] compared for their reactivity towards DNA model systems. Issue 20 (29th April 2016) - Musumeci, Domenica; Platella, Chiara; Riccardi, Claudia; Merlino, Antonello; Marzo, Tiziano; Massai, Lara; Messori, Luigi; Montesarchio, Daniela
Abstract : The reactivity of cis -PtI2 (NH3 )2 with selected DNA model systems, in single, double strand or G-quadruplex form, has been studied by circular dichroism, UV-visible spectroscopy and electrospray mass spectrometry using cisplatin as a control. Abstract : Contrary to what was believed for many years, cis -PtI2 (NH3 )2, the diiodido analogue of cisplatin, displays high in vitro antiproliferative activity toward a set of tumour cell lines, overcoming resistance to cisplatin in a platinum-resistant cancer cell line. In the context of a general reappraisal of iodinated Pt(ii ) derivatives, aiming at a more systematic evaluation of their chemical and biological profiles, here we report on the reactivity of cis -PtI2 (NH3 )2 with selected DNA model systems, in single, double strand or G-quadruplex form, using cisplatin as a control. A combined approach has been exploited in this study, including circular dichroism (CD), UV-visible spectroscopy and electrospray mass spectrometry (ESI-MS) analyses. The data reveal that cis -PtI2 (NH3 )2 shows an overall reactivity towards the investigated oligonucleotides significantly higher than cisplatin.